(untitled) (Journal of the College of Basic Education, 2022)
In this paper, some properties concerning orthonormal Bernstein polynomials are derived. An explicit formula for the derivative orthonormal Bernstein polynomials of degree five is obtained in terms of Bernstein polynomials themselves to construct the operational matrix of derivatives of orthonormal Bernstein polynomials. Then we apply it for solving calculus of variational approximately using direct method. Illustrative example is given to demonstrate the efficiency of the method.